Induction of endocycles represses apoptosis independently of differentiation and predisposes cells to genome instability. - Hassel, C.; Zhang, B.; Dixon, M.; Calvi, B.R. (Development, 2014)
The endocycle is a common developmental cell cycle variation wherein cells become polyploid through repeated genome duplication without mitosis. We previously showed that Drosophila endocycling cells repress the apoptotic cell death response to genotoxic stress. Here, we investigate whether it is differentiation or endocycle remodeling that promotes apoptotic repression. We find that when nurse and follicle cells switch into endocycles during oogenesis they repress the apoptotic response to DNA damage caused by ionizing radiation, and that this repression has been conserved in the genus Drosophila over 40 million years of evolution. Follicle cells defective for Notch signaling failed to switch into endocycles or differentiate and remained apoptotic competent. However, genetic ablation of mitosis by knockdown of Cyclin A or overexpression of fzr/Cdh1 induced follicle cell endocycles and repressed apoptosis independently of Notch signaling and differentiation. Cells recovering from these induced endocycles regained apoptotic competence, showing that repression is reversible. Recovery from fzr/Cdh1 overexpression also resulted in an error-prone mitosis with amplified centrosomes and high levels of chromosome loss and fragmentation. Our results reveal an unanticipated link between endocycles and the repression of apoptosis, with broader implications for how endocycles may contribute to genome instability and oncogenesis.